ANTHELMINTICS AND ANTHELMINTIC RESISTANCE AGAINST GASTROINTESTINAL NEMATODES OF SMALL RUMINANTS - G. Amulya; R. Sudharani; M. Ismail Shareef; S.M. Gopinath (Indian Journal of Veterinary and Animal Sciences Research, 2024)
Gastrointestinal nematode parasitism is one of the major factors limiting sheep production worldwide because they cause heavy economic losses in meat and wool production. Gastrointestinal parasitism is the major cause for morbidity and mortality in ruminants. Severe anemia, reduction in functional gastric gland mass, severe damage to gastric mucosa and villous astropy caused by these worms are responsible for the death due to parasitic gastroenteritis. In India, the common nematode species encountered is Haemonchus contortus in small ruminants. This review throws light on the different mechanisms and contributory factors affecting the development of anthelmintic resistance, the diagnosis and means to prevent the resistance at field level. The emergence of multi-resistant nematode has shown that the previously used control strategies is no longer a chemically success method. The interpretation of fecal egg count reduction test has been modified and suggestions are made on its use with persistent anthelmintics.